Quantum states cannot be transmitted efficiently classically - Ashley Montanaro (Quantum, 2019)
We show that any classical two-way communication protocol with shared randomness that can approximately simulate the result of applying an arbitrary measurement (held by one party) to a quantum state of $n$ qubits (held by another), up to constant accuracy, must transmit at least $Ω(2^n)$ bits. This lower bound is optimal and matches the complexity of a simple protocol based on discretisation using an $ε$-net. The proof is based on a lower bound on the classical communication complexity of a distributed variant of the Fourier sampling problem. We obtain two optimal quantum-classical separations as easy corollaries. First, a sampling problem which can be solved with one quantum query to the input, but which requires $Ω(N)$ classical queries for an input of size $N$. Second, a nonlocal task which can be solved using $n$ Bell pairs, but for which any approximate classical solution must communicate $Ω(2^n)$ bits.